EFEKTIVITAS TUGAS DAN WEWENANG INSPEKTORAT DAERAH KOTA PALOPO PERSPEKTIF SIYASAH DUSTURIYAH - Yusuf, Albab Hoalidi'n; Maloko, M. Thahir; Halimang, St (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
This research is entitled Effectiveness of Duties and Authority of Regional Inspectorate of Regional Inspectorate of Palopo City?, Perspective of Siyasah Duturiyah. The main research problem is how effective the duties and authorities of the regional inspectorate of Palopo City are from the perspective of Siyasah Duturiyah? .This type of research is a qualitative descriptive field research using a normative juridical approach and a syar'i approach. The results showed that Implementation of the duties and authorities of the Palopo City Regional Inspectorate in the form of an audit, a review, an evaluation, monitoring and assistance. The review is here to ensure that what we are going to do is in accordance with the laws and regulations.second Obstacles experienced by the Palopo City Regional Inspectorate, namely. First, the Limited Number of Government Internal Supervisory Apparatus (APIP). Second, Budget Limitations. third The perspective of Siyasah Dustruiyah in carrying out the duties and authorities of the Palopo City Regional Inspectorate in carrying out its supervisory function has not used the Islamic concept or the Siyasah dustruiyah concept, because the implementation of the duties and authorities of the Palopo City Regional Inspectorate is guided by the provisions of the applicable laws and regulations. Meanwhile, in Islamic law the implementation of the supervisory function is carried out with the concepts of hisbah and muraqabah.